IMPLEMENTATION OF E-FORECASTING ON JIMMY FISH USING THE WIEGHTED MOVING AVERAGE METHOD - Triana Sri Gunarti; Baibul Tujni; Imam Solikin (STMIK Royal, 2023)
Abstract: This research is a development of previous research, where the results of previous studies have only arrived at the application design stage. Jimmy Fish UMKM is a business that sells fish seeds, while the fish seeds that are sold are: catfish, tilapia, goldfish, mujaer fish, catfish, and carp. Jimmy Fish UMKM has several activities to support its business, one of which is determining how much stock of fish fry is needed for each period. Jimmy Fish SMEs have problems in determining the amount of fish seed stock, Jimmy Fish SMEs still use estimates without definite calculations to determine the number of fish seed stocks. As a result of this problem, when someone wants to buy fish seeds, the number of stocks is not fulfilled (less), the number of fish seeds is depleted, and there is even an excess stock of fish seeds (only a few sold), so that activities at Jimmy Fish SMEs become less effective. The solution to the existing problems is to build an e-forecasing application using the wieghted moving average (WMA) method. The e-forecasting application is very important because it can predict the number of fish seed stocks for the next period using calculations from previous data. The e-forecasting application also provides convenience, speed and as a support system for making decisions on how many fish seed stocks must be fulfilled for the next period.Keywords: applications; e-forecasting; WMA Abstrak: Penelitian ini merupakan pengembangan dari penelitian sebelumnya, dimana hasil dari penelitian sebelumnya baru sampai pada tahap desain aplikasi. UMKM Jimmy Fish merupakan usaha yang menjual bibit ikan adapun bibit ikan yang dijual yaitu: ikan lele, ikan nila, ikan emas, ikan mujaer, ikan patin, dan ikan gurame. UMKM Jimmy Fish mempunyai beberapa aktifitas untuk mendukung usahanya salah satunya penentuan berapa jumlah stok bibik ikan yang diperlukan untuk setiap periodenya. UMKM Jimmy fish mempunyai permasalahan dalam menentukan jumlah stok bibit ikan, UMKM Jimmy Fish masih menggunakan perkiraan tanpa perhitungan yang pasti untuk menentukan jumlah stok bibit ikan. Akibat yang ditimbulkan dari permasalah tersebut, ketika ada yang ingin membeli bibit ikan jumlah stok tidak terpenuhi (kurang), jumlah stok bibit ikan habis, dan bahkan ada jumlah stok bibit ikan yang berlebih (hanya terjual sedikit), sehingga aktifitas pada UMKM Jimmy Fish menjadi kurang efektif. Solusi dari permasalah yang ada, dengan membangun aplikasi e-forecasing menggunakan metode wieghted moving average (WMA). Aplikasi e-forecasting sangat penting karena dapat prediksikan jumlah stok bibit ikan untuk periode selanjutnya menggunakan perhitungan dari data-data sebelumnya. Aplikasi e-forecasting juga memberikan kemudahan, kecepatan dan sebagai support system pengambilan keputusan berapa jumlah stok bibit ikan yang harus terpenuhi untuk periode selanjutnya.Kata kunci: aplikasi; e-forecasting; WMA